Analysis of Snakehead Fish (Channa striata) Cultivation Business in Peatland, Dadahup Village, Kapuas Regency, Indonesia - Khairul Anwar; Muhammad Faiq Naufal; Hany Handajani; Soni Andriawan (IJOTA (Indonesian Journal of Tropical Aquatic), 2020)
Snakehead fish (Channa striata) is a popular freshwater commodity with high market demand in Indonesia, especially in Central Kalimantan. Kapuas Regency, there is a group of farmers who utilize the productivity of peatland to be used as a medium of cultivation of snakehead fish through a biological approach. This research aims to analyze the efforts of members of the fish cultivation group Bahtera Handal Dadahup (BHD), Kapuas Regency based on business analyze to determine the net profit value (π), R/C ratio, Payback Period (PP), and Break Even Point (BEP). BHD group obtained a value ranging from Rp 11 935 000 to Rp 46 022 500; R/C > 1, i.e. ranging from 2.96 to 4.29. Payback Period or return period of capital (investment) lasts for 5 to 10 months; and break even point (BEP) values range from Rp 9 318.3 kg-1 to Rp 13 477.7 kg-1. Based on the calculation of the analysis of the business, the business of fish cultivation group Bahtera Handal Dadahup, deserves to be run and developed.